Evaluation of healing effect of commercial sugar compared to fusidic acid in rabbit skin - Sudario Arainga, Judith Soledad (2019)
Objective: To evaluate the healing effect of commercial sugar compared to 2% fusidic acid in wounds induced in rabbit skin. Materials and Methods: Qualitative experimental, observational, in vivo analytical study in rabbits with skin lesions. Wound were treated with blond sugar (10 and 20 g) directly applied and also with 2% fusidic acid. By comparative study, the effectiveness of the treatment in the lesions was evaluated. Results: Sucrose was effective to cure wounds and stimulate healing in rabbits, obtaining similar results to fusidic acid at 2%, granulation tissue was observed early, which allowed to observe the healing phases with 10 days of treatment. Conclusions: it was demonstrated the pharmacological healing effect of sucrose similar to 2% fusidic acid directly (20 g).